2014
DOI: 10.1002/app.41325
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amorphous alkaline lignin on the crystallization behavior and thermal properties of bacterial polyester

Abstract: Bacterial polyester poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and alkaline lignin composites were prepared via melt processing method, and the influence of amorphous lignin on the crystallization behavior and thermal properties of PHBV were investigated. It was found that dual melting peaks appeared in DSC curves of PHBV/lignin composites, while only one single peak existed in PHBV. The non-isothermal crystallization process analyzed by Jeziorny method suggested that lignin changed the nucleation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…At low CNT contents, the increase in T m could be interpreted by the generation of small PHBV spherulites with higher perfection (see Figure ) induced by the heterogeneous nucleation of CNTs . At higher CNT concentrations, the T m of PHBV specimens decreased slightly due to the agglomeration of CNTs (see Figure i), which restrained the movement of PHBV molecule chains and damaged the perfection degree of PHBV crystallites . These findings were similar to the results reported by Sanchez …”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At low CNT contents, the increase in T m could be interpreted by the generation of small PHBV spherulites with higher perfection (see Figure ) induced by the heterogeneous nucleation of CNTs . At higher CNT concentrations, the T m of PHBV specimens decreased slightly due to the agglomeration of CNTs (see Figure i), which restrained the movement of PHBV molecule chains and damaged the perfection degree of PHBV crystallites . These findings were similar to the results reported by Sanchez …”
Section: Results and Discussionsupporting
confidence: 90%
“…42 At higher CNT concentrations, the T m of PHBV specimens decreased slightly due to the agglomeration of CNTs (see Figure 3i), which restrained the movement of PHBV molecule chains and damaged the perfection degree of PHBV crystallites. 43 These findings were similar to the results reported by Sanchez. 20 POM Analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The addition of lignin already in the concentration of 1 wt.% modified the crystallization and the melting behavior of PHBHV. For example, Shichao and coworkers reported that alkaline lignin hindered crystallization of PHBHV [39]. Thermal data determined from heating-cooling-heating thermograms are displayed in Table 3.…”
Section: Thermal Behavior Of Phbhv Filmsmentioning
confidence: 99%
“…Similarly, sugar cane bagasse lignin modified thermal decomposition behavior of PHBHV and deteriorated mechanical properties of PHBHV [34]. Shichao et al [39] reported a modified crystal structure of PHBHV and a decrease of its thermal stability due to an incorporation of 1-10% alkaline lignin. We hypothesize that influence of lignin on PHBHV depends on their interfacial compatibility.…”
Section: Introductionmentioning
confidence: 97%
“…The effect of lignin content on the isothermal and nonisothermal crystallization kinetics of different polymeric materials has been reported, but none of them deals with PCL. Additionally, a considerable amount of articles study properties of polymer/lignin blends, but crystallization kinetics are not considered.…”
Section: Introductionmentioning
confidence: 99%